2019
DOI: 10.1016/j.fertnstert.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early in vitro fertilization treatment discontinuation

Abstract: Objective: To investigate factors associated with early in vitro fertilization (IVF) treatment discontinuation. Design: Retrospective cohort study. Setting: High-volume Midwestern academic medical center. Patient(s): Six hundred sixty-nine first-attempt IVF patients who did not have a live birth. Intervention(s): None. Main Outcome Measure(s): Treatment discontinuation and time to return for a second IVF cycle. Result(s):Women without IVF insurance coverage were more likely to discontinue treatment than women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…It has been stated that insurance coverage of ART is associated with higher utilization and improvements in practice [9,18,19]. However, this also raises the question of whether this disparity in participation represented a difference in economic access to ART [20][21][22] and/or whether other unidentified social and/or culture factors associated with race underlined such a difference [23,24]. Despite these observations of disparity in access, cycle LBRs (outcomes) were not significantly different between black and white women based upon the presence or absence of state insurance mandates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that insurance coverage of ART is associated with higher utilization and improvements in practice [9,18,19]. However, this also raises the question of whether this disparity in participation represented a difference in economic access to ART [20][21][22] and/or whether other unidentified social and/or culture factors associated with race underlined such a difference [23,24]. Despite these observations of disparity in access, cycle LBRs (outcomes) were not significantly different between black and white women based upon the presence or absence of state insurance mandates.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, many previous studies have examined and identified several factors that lead people to discontinue infertility treatment. Several identified predictors of discontinuation are related to patients, clinics, and their relationships, including the patients’ physical and psychological burdens, their limited financial resources, inadequate organization of care, poor communication skills of staff, and negative interactions between the patients and staff 9‐14 . Additionally, other studies have found that female age, duration of subfertility, other maternal conditions, and stressful life events were key factors in determining the success of the infertility treatment 15‐18 …”
Section: Introductionmentioning
confidence: 99%
“…The dropout of fertility treatments refers to the further treatment despite the favorable progress and the ability to pay for treatment that can occur at any stage of the treatment [8]. The prevalence of discontinuation varies from 5.6% to 70% in different studies [9][10][11][12][13][14][15]. In Iran, the rate of discontinuation of treatment was 56.5% in one study [16] and 28.3% in another study [17].…”
Section: Introductionmentioning
confidence: 99%